0021 Lower Oxygen Saturation During Sleep Is Associated With Reduced Expressions Of Cd1d And Rab20 That Is Potentially Reversed By CPAP Therapy. (12th April 2019) - Sofer, Tamar; Li, Ruitong; Joehanes, Roby; Lin, Honghuang; Gower, Adam; Punjabi, Naresh; Mehra, Reena; Patel, Sanjay; Quan, Stuart; Liu, Yongmei; Gharib, Sina; Levy, Daniel; et al.
Abstract: Introduction: Obstructive Sleep Apnea (OSA) is associated with a wide range of physiological changes, many of which are secondary to overnight hypoxemia. Prior associations studies of OSA and gene expression in blood were performed in small, clinic based samples. Here we study OSA and hypoxemia-related gene expression associations in large population-based studies, and in a small sample of individuals with OSA before and after treatment using continuous positive airway pressure (CPAP) who participated in the Heart Biomarkers in Apnea Treatment Study (HeartBEAT). Methods: We performed discovery analysis in two population-based studies: the Multi-Ethnic Study of Atherosclerosis (MESA; N = 580), and the Framingham Heart Study (FHS; N=571). We studied the association of gene expression in blood with three correlated traits that characterize the severity of OSA: the Apnea Hypopnea Index (AHI), defined as the number of apnea and hypopnea events accompanied by oxygen desaturation of at least 3% experienced per hour of sleep; average oxygen saturation (AveO2); and minimum oxygen saturation (minO2) during sleep. Associations with FDR q-value<0.05 in one study and p-value<0.05 in the other study, or with FDR q-value<0.05 in a meta-analysis of FHS and MESA, were then tested for gene expression change in the blood of 15 participants from the HeartBEAT study who had moderate or severe OSA and were studied before and after three months of treatment with CPAP. Results: We identified 22 genes associated with OSA traits in both MESA and FHS, with most associations observed in AveO2 and minO2. Two of these genes further showed evidence of change with treatment in HeartBEAT: Lower CD1D and RAB20 expressions were associated with lower AveO2 in MESA and FHS, and CPAP therapy increased their expression in HeartBEAT. Conclusion: Gene expressions in CD1D and RAB20 were associated with OSA traits and appear to respond to CPAP therapy. CD1D encodes the CD1d antigen, and is associated with autoimmune diseases; RAB20 is a GTPase enzyme which is a Hypoxia-inducible transcription factor (HIF) target. Support (If Any): R35 HL135818.